Going for a stroll on lurasidone: Considerations on an atypical case of acute compartment syndrome of both legs. Issue 4 (April 2023) - Bosco, L.; Russo, T.; Falzone, Y.M.; Butera, C.; Del Prete, A.; Mellone, R.; Del Carro, U.; Filippi, M.; Previtali, S.C.
Abstract: Non-traumatic acute bilateral compartment syndrome is a rare condition that may lead to limb ischemia. We describe a case of this syndrome occurring after a five-kilometer walk in a young woman receiving chronic treatment with lurasidone, leading to a bilateral foot-drop and rhabdomyolysis of the anterolateral compartment of both legs. Due to her late presentation in the emergency department, we opted for a conservative approach, closely monitoring her renal function. We noticed a subsequent clinical and biochemical improvement over the following days, with the patient returning to her daily routine in a matter of weeks, despite a persisting bilateral foot drop. Since atypical antipsychotics are known to be associated with rhabdomyolysis, while possibly exerting a toxic effect on mitochondria, we hypothesize that a mild aerobic physical exertion might have triggered the event, in the context of an iatrogenic muscle susceptibility to oxidative distress.